IMPLEMENTASI PROGRAM EDUKASI PARENTING DALAM MENINGKATKAN KUALITAS PENGASUHAN ANAK ERA DIGITAL DI DESA NGADIROJO - Kenlies Era Rosalina Marsudi; Wanda Soraya Putri; Ainaya Salsabila; Dhinar Setya Rahayu (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2026)
Parenting knowledge is a fundamental foundation that parents must master as the main provision for shaping children's character. Currently, cultural shifts, civilizational transformations, and technological disruptions have significantly impacted interaction and parenting patterns. However, not all parents comprehend the detrimental effects of technological exposure on child development. The emergence of various issues related to child and adolescent delinquency has become an alarming threat to parents. Consequently, this community service program aims to provide parenting education to address contemporary challenges and alleviate parental anxiety. This activity specifically targets a group of 30 mothers residing in Krajan Hamlet, Ngadirojo Village, Sooko District. The program was implemented using the Asset-Based Community Development (ABCD) method, encompassing four primary stages: discovery, design, define, and reflection. Through this educational initiative, it is anticipated that parents' understanding of parenting styles relevant to the digital era will improve. Furthermore, the program endeavors to cultivate a parental mindset emphasizing the importance of active involvement in monitoring, guiding, and listening to their children's aspirations.